Digital Parasites: Reassessing Notions of Autonomy and Agency in Posthuman Subjectivity - Bolton, Michael Sean (Theoria and Praxis: International Journal of Interdisciplinary Thought, 2014)
This article offers a composite of the concepts of the parasite from Michel Serres’s work The Parasite, and of the digital subject of N. Katherine Hayles’s My Mother Was a Computer in order to provide a model for better understanding the operation of autonomy and agency in the formation of posthuman subjectivity. For Serres, interactions between subjects are always instigated and mediated by a third party, a parasitical noise that both interrupts and orders communication. Serres’s subject as parasite resembles the digital subject postulated by Hayles, in that the digital subject also depends on fragmentation for its complexity and growth. However, Hayles’s subject offers a possibility for agency that is not possible with Serres’s analog model. The composite I propose, the digital parasite, enables an autopoietic process that reassesses the autonomy and agency of the subject. The article seeks to explore and understand how re-conceptions of autonomy and agency within this autopoietic process can be applied to theorizing the posthuman as an extension of, rather than a departure from, the humanist subject.